2019
DOI: 10.1007/s00134-019-05667-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing PEEP on lung stress and strain in children with and without ARDS

Abstract: The ratio of tidal volume to functional residual capacity (FRC), defined as "volumetric" strain, causes physical lung deformation. The corresponding change in transpulmonary pressure at end inspiration, defined as stress, is directly applied to the alveolus [1]. Both stress and strain may cause global or local lung deformation and microscopic or macroscopic tissue damage, representing significant determinants of ventilator-induced lung injury [1]. A modified nitrogen washout/washin technique, measuring end-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Small tidal volume combined with PEEP has been widely used in the clinical treatment of acute lung injury and has achieved good clinical results. However, with the increase in PEEP, the venous return flow may be decreased, and the arterial vascular resistance will be increased, which may affect cardiac output and increase the risk of lung injury, especially for elderly patients under general anesthesia[ 15 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small tidal volume combined with PEEP has been widely used in the clinical treatment of acute lung injury and has achieved good clinical results. However, with the increase in PEEP, the venous return flow may be decreased, and the arterial vascular resistance will be increased, which may affect cardiac output and increase the risk of lung injury, especially for elderly patients under general anesthesia[ 15 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 The steadily increased strain and stress related to ARDS in this study assumes that this phenomenon is more exacerbated in subjects with ARDS compared to subjects at risk for ARDS, expanding results of previous studies that reported higher strain and stress in adults and in children with lung injury compared to healthy individuals. 14,27 The "lung injury" limits for strain may be exceeded by increasing the V T in patients with low C RS . Depending on recruitment potential, static hyperaeration produced by unnecessarily high PEEP might add tidal (dynamic) volume to the static hyperinflation.…”
Section: Discussionmentioning
confidence: 99%
“…1186/ s13054-022-04084-z. *Correspondence: ggbriass@otenet.gr; briasoug@uoc.gr 1 Postgraduate Program "Emergency and Intensive Care in Children Adolescents and Young Adults", Pediatric Intensive Care Unit, School of Medicine, University of Crete, Section 6D (Delta), Office 03, Voutes, 71003 Heraklion, Crete, Greece Full list of author information is available at the end of the article but not compliance (Crs), increased from PEEP 4 to PEEP 10 cmH 2 O (p = 0.001) in ARDS pediatric patients longitudinally [3]. Previous experimental and clinical studies have similarly questioned the reliability of Crs for lung recruitment/derecruitment estimation in ARDS.…”
Section: Open Accessmentioning
confidence: 99%
“…Personalizing PEEP to target optimal compliance might identify ARDS patients with functional lung units, avoiding the indiscrete application of high PEEP [ 2 ]. Using the nitrogen washout/washin technique, we have recently demonstrated that end-expiratory lung volume (EELV), but not compliance (Crs), increased from PEEP 4 to PEEP 10 cmH 2 O ( p = 0.001) in ARDS pediatric patients longitudinally [ 3 ]. Previous experimental and clinical studies have similarly questioned the reliability of Crs for lung recruitment/derecruitment estimation in ARDS.…”
mentioning
confidence: 99%